1999
DOI: 10.1038/eye.1999.56
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of contact lenses without tap water rinsing: Is it effective?

Abstract: Purpose To establish the efficacy of the two most popular contact lens disinfecting systems -one-step hydrogen peroxide and multi purpose disinfecting solution -for 1 month's use in practice in the absence of tap water rinsing.Methods This was a descriptive, prospective microbiological study of contact lens contamination with ideal hygiene compliance and new lenses and storage cases. One hundred and fifty contact lens wearers were instructed to avoid risk factors identified for Acanthamoeba infection. They wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Education of the contact lens-wearing public with informed preventive measures, such as avoidance of overnight (sleeping) wear of hydrogel contact lenses, non-smoking and use of sterile multi-purpose solutions in lens storage cases without tap water, 18 should be cost-effective in reducing the incidence of lensassociated MK in Hong Kong and elsewhere. These measures will be complemented by new ideas such as the incorporation of salicylate into multipurpose solutions, to prevent the formation of biofilm on lenses and the adherence of microbes including Acanthamoeba to them within the storage case.…”
Section: Albeit In the Eyementioning
confidence: 99%
“…Education of the contact lens-wearing public with informed preventive measures, such as avoidance of overnight (sleeping) wear of hydrogel contact lenses, non-smoking and use of sterile multi-purpose solutions in lens storage cases without tap water, 18 should be cost-effective in reducing the incidence of lensassociated MK in Hong Kong and elsewhere. These measures will be complemented by new ideas such as the incorporation of salicylate into multipurpose solutions, to prevent the formation of biofilm on lenses and the adherence of microbes including Acanthamoeba to them within the storage case.…”
Section: Albeit In the Eyementioning
confidence: 99%
“…Swimming, diving, showering or washing the face while wearing contact lenses was reported to cause Acanthamoeba keratitis. 97,[104][105][106][107][108] The 50-fold increase in the risk of Acanthamoeba keratitis among disposable contact lens users was largely attributable to repeated wear of lenses, lack of disinfection, and use of saline and chlorine-based solutions. 75 The compliance of contact lens users with the recommended care procedures is ineffective if these solutions do not manage to kill Acanthamoeba.…”
Section: Non-compliant Contact Lens Usersmentioning
confidence: 99%
“…The use of tap water for the care of contact lenses was widely accepted as the main risk factor in Acanthamoeba infection. 5,85,[97][98][99][100][101][102] In the United Kingdom, 91% of the soft contact lens wearers and 94% of the rigid lens wearers avoided the disease by the complete avoidance of water and the use of powerful lens disinfecting solutions. 5 In the USA, the withdrawal of salt tablets from the market was responsible for the decrease in the incidence of Acanthamoeba keratitis in the mid 80s.…”
Section: Non-compliant Contact Lens Usersmentioning
confidence: 99%
“…The influence of tap water on the presence of Acanthamoeba in CL maintenance was investigated by Seal et al [60]. This study involved the recruiting of 150 CL wearers and careful instruction was given to these patients with respect to possible risk factors for the development of Acanthamoeba infection.…”
Section: Contaminated Solutionsmentioning
confidence: 99%
“…They were instructed to avoid use of tap water (except for hand washing). They were randomly assigned to one of three disinfecting (two one-step hydrogen peroxide and one multipurpose solution) systems [60]. Results after 1 month’s use consequently demonstrated that Acanthamoeba was not found in any of the 150 cases.…”
Section: Contaminated Solutionsmentioning
confidence: 99%